Draft Fourth Five-Year Plan (1969-74) of Chandigarh Union Territory - Planning Commission (Planning Commission, 1969)
With the reorganisation of Punjab on the 1st November, 1966, about 52 villages of Kharar Tehsil of erstwhile Ambala District constituted Union Territory of Chandigarh, the lands of about 24 villages had already been acquired for the development of first phase of Chandigarh Capital for catering to a population of 1.5 lakhs. 15 more villages were to be wholly or partially acquired for the development of second phase of this city and the bulk of area in these villages has already been acquired. the remaining 13 villages form the rural part of the Union Territory which has an approximate population of 40,000 souls.
Chandigarh Administration